PENINGKATAN KEMAMPUAN LITERASI PESERTA DIDIK MELALUI KEGIATAN KAMPUS MENGAJAR DI SMP NEGERI 3 TENGGARONG SEBERANG KUTAI KARTANEGARA - Jamil, Muhammad Sajid; Ahmadi, Amelia Hardiyanti; Palapa, Kaleb G.; Subaer, Sukma; Komaria, Winda; Cahyaningrum, Gyta Krisdiana; Cahyono, Didik (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
The numeracy literacy program is a program that aims to improve the quality of education that supports the Class 6 Teaching Campus Program. This service method is in the form of a qualitative approach. The location of the service was held at SMP Negeri 3 Tenggarong Seberang, participants in this activity included 30 class VIII students. Data collection uses observation techniques, interviews, documentation, as well as AKM pre-tests and post-tests. The results of the community service show that the implementation of the campus teaching program for class 6 through collaborative activities of the numeracy literacy implementation program was carried out, including: making school posters, reading movements 15 minutes before learning, language month activities, and literacy learning in class, numeracy icebreakers, snakes numeracy ladder, Literacy Quiz and application of technology adaptation. The results of the implementation of this program were able to increase students' AKM scores in literacy by 8% and numeracy by 3%. It can be concluded that the implementation of the numeracy literacy program through class 6 teaching campuses can improve numeracy literacy skills.